2019
DOI: 10.5935/1518-0557.20190056
|View full text |Cite
|
Sign up to set email alerts
|

Immature oocyte incidence: Contributing factors and effects on mature sibling oocytes in intracytoplasmic sperm injection cycles

Abstract: Objective: The aim of this study was to investigate which factors contribute to the incidence of immature oocytes (germinal vesicle-GV-and metaphase I-MI-) and how they impact the intracytoplasmic sperm injection (ICSI) outcomes of sibling mature oocytes. Methods: Data from 3,920 cycles performed from June/2010 to August/2016 in a private university-affiliated IVF center were evaluated for the influence of controlled ovarian stimulation protocol (COS) on immature oocytes incidence and its effects on ICSI outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…We found a rescued maturation rate of 57% of MI oocytes after 4 hours of incubation in culture medium, and these rates were similar to those of other studies that reported rates between 43 and 54% in the first 4-6 hours (Shu et al, 2007;Vanhoutte et al, 2005;Álvarez et al, 2013). Regarding incubation time, Strassburger et al (2004) found that 13% of MI oocytes subjected to rescue maturation matured within 1 hour and that another 41% matured within 2.5 hours, revealing that most MI oocytes (54%) matured in vitro to MII oocytes after 2.5 hours of incubation; however, the performance of these oocytes with respect to embryonic development appears to be reduced compared with MII oocytes (Braga et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a rescued maturation rate of 57% of MI oocytes after 4 hours of incubation in culture medium, and these rates were similar to those of other studies that reported rates between 43 and 54% in the first 4-6 hours (Shu et al, 2007;Vanhoutte et al, 2005;Álvarez et al, 2013). Regarding incubation time, Strassburger et al (2004) found that 13% of MI oocytes subjected to rescue maturation matured within 1 hour and that another 41% matured within 2.5 hours, revealing that most MI oocytes (54%) matured in vitro to MII oocytes after 2.5 hours of incubation; however, the performance of these oocytes with respect to embryonic development appears to be reduced compared with MII oocytes (Braga et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding incubation time, Strassburger et al . (2004 ) found that 13% of MI oocytes subjected to rescue maturation matured within 1 hour and that another 41% matured within 2.5 hours, revealing that most MI oocytes (54%) matured in vitro to MII oocytes after 2.5 hours of incubation; however, the performance of these oocytes with respect to embryonic development appears to be reduced compared with MII oocytes ( Braga et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different COS protocols entail different combinations of hormones that may lead to follicular asynchrony and variations in the quantity, quality, viability, and competence of oocytes. Therefore, it is extremely important to analyze the quantity and quality of stimulation given to patients (Braga et al, 2020;Quaas & Legro, 2019) It is important that patients undergo preparation before the initiation of COS. To facilitate scheduling for women undergoing treatment and ART centers, combined oral contraceptives (COC) have been prescribed prior to the initiation of treatment cycles to schedule and date menstruation. According to studies (Biljan et al, 1998;Griesinger et al, 2008), the use of COC provides other advantages, such as improved follicular timing during ovulation stimulation, lower cancellation rates in hyper-responsive women, and greater number of aspirated oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The protocols generally comprise of administering a combination of gonadotrophin analogs namely gonadotropins-releasing hormone (GnRH) agonist or antagonist, estradiol inhibitors, recombinant follicle-stimulating hormone (FSH), and luteinizing hormone (LH) (Gallos et al, 2017). While the drug regimens hold paramount importance for IVF and have been established and refined through years of clinical practice and research, the incidence of asynchronous ovarian response persists (Braga et al, 2020). This is evident in the miscellaneous yield of abnormal, immature, and poor-quality oocytes at retrieval.…”
Section: Introductionmentioning
confidence: 99%